Edukasi Keselamatan Pelayaran melalui Penyuluhan tentang Safety Equipment (Alat Keselamatan) - Endah Fauziningrum; Iwan Mahendro; Kusdibyo Kusdibyo; Mariana Kristiyanti; Renny Hermawati (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The fishermen have a very high-risk work. It is prone to accidents. They are related to nature factors and the length of time they go to sea. The existence and use safety equipment in accordance with standards can minimize the risk accidents and injuries, so it can avoid fatal consequences. This community service activity needs to be carried out for counseling or socialization or training regarding materials/messages related to efforts to prevent work accidents due to unsafe acts, especially with protective equipment, safety equipment, and the dangers of joking in the workplace, guidance to traditional fishermen about safety and health, considering that this group is widely available along fishing ports, first aid materials for accidents and lifesaving. This activity descriptive and practice method. Universitas Maritim AMNI carries out this community service activity in the context of preventing fishermen's work accidents to improve the knowledge, attitudes, and practices of fishermen in vigilance and action in dealing with accidents at sea.